PENGARUH VARIASI DIAMETER PIPA INPUT DAN PIPA OUTPUT TERHADAP KINERJA POMPA HIDRAM - budi santoso wibowo (Machine : Jurnal Teknik Mesin, 2019)
Bangka Belitung Province is one of the provinces that have a vast potential of agricultural land, with the potential for abundant water resources in an area that is often in contradiction with the conditions in which some regions still lack water. Often the source of water is under the location of settlements or agricultural land, so it is difficult to use it. The use of electric/diesel pumps has significant cost consequences, as some farmers do use diesel pumps to irrigate their farm fields from rivers that are nearby. One technology that is simple and inexpensive to use is the use of a hydram pump. The methodology in this study is that the hydram pump drive is derived from the impact of water entering the pump through a pipe that depends on the flow of flow entering the pump. This study discusses the performance of hydram pumps on variations in the diameter of the Input pipe and Output pipe. The results of the study that the greatest efficiency of hydram pump for discharge of 8 liters/minute is in the variation of the diameter of the Input pipe 1 inch and the Output pipe 1½ inches is 9.5%, while the lowest efficiency in the variation of the Input pipe diameter is 1½ inches and the Output pipe 1½ inches is 6, 2%. The results of the study found that the larger the diameter of the Input pipe and the smaller the diameter of the Output pipe, the greater the efficiency produced at the hydram pump.